Designing a Web-based Room Service System - Sudarto, Ferry; Hapsari, Fatma Azzahra (Aptisi Transactions On Technopreneurship (ATT), 2019)
In the digital era, almost all activities are done computerized. Now the internet is widely used in business activities. In the field of internet business used for marketing, usually marketing is done through a website of a company. This method is quite powerful in overcoming the limited time for marketing a product company. However, not all business activities do this way of marketing. One business activity that has not fully to use the internet in marketing its products is hotels, hotel has room service services which is still done manually. This way is still less effective against marketing room service services, for it is necessary for a web-based computerized system that can overcome these shortcomings. This research methodology uses SDLC (System Development Life Cycle) through the planning, analysis, design and implementation phase. The final result of this design are a website that can facilitate in overcoming the reservation service room service at hotels.